2009
DOI: 10.1590/s0100-204x2009001000008
|View full text |Cite
|
Sign up to set email alerts
|

Resistência mediada por aleloquímicos de genótipos de tomateiro à mosca-branca e ao ácaro-rajado

Abstract: O objetivo deste trabalho foi comparar os graus de resistência à mosca-branca (Bemisia argentifolii) e ao ácaro-rajado (Tetranychus urticae) de híbridos de tomateiro resultantes do cruzamento entre linhagens com alto teor de zingibereno (ZGB) e linhagens com alto teor de acilaçúcar (AA), em contraste com as linhagens parentais e testemunhas comerciais. Foram avaliadas linhagens com altos teores de AA, linhagens com alto teor de ZGB, híbridos duplos heterozigotos ZGB+AA, híbridos heterozigotos para ZGB e híbrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
2
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 15 publications
7
27
2
8
Order By: Relevance
“…IV = type IV trichome; VI = type VI trichome ;Gland = glandular density. Analogous results with the allelochemicals AS and ZGB were found by Silva et al (2009), in which AS-rich (TOM-688 and TOM-689) and ZGB-rich (ZGB-703 and ZGB-704) lines exhibited greater resistance to the silverleaf whitefly. However, Silva et al (2009) observed that ZGB was significantly more efficient than AS in reducing number nymphs, indicating that ZGB may bestow a higher degree of antixenosis than AS.…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…IV = type IV trichome; VI = type VI trichome ;Gland = glandular density. Analogous results with the allelochemicals AS and ZGB were found by Silva et al (2009), in which AS-rich (TOM-688 and TOM-689) and ZGB-rich (ZGB-703 and ZGB-704) lines exhibited greater resistance to the silverleaf whitefly. However, Silva et al (2009) observed that ZGB was significantly more efficient than AS in reducing number nymphs, indicating that ZGB may bestow a higher degree of antixenosis than AS.…”
Section: Resultssupporting
confidence: 65%
“…For the purpose of infestation by B. tabaci biotype B, as previously identified and used by Silva et al (2009) and Maluf et al (2010), silverleaf whiteflies were grown in a protected greenhouse with a 12-m 2 domed protective structure covered by transparent plastic. Adult insects were randomly collected at several tomato cv.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations